2009
DOI: 10.1007/s11420-009-9110-2
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Neuropathy at the Wrist

Abstract: A case of ulnar nerve compression at the wrist within Guyon's canal is reported. The clinical presentation initially appeared consistent with an ulnar nerve entrapment at the elbow. The true diagnosis of an ulnar sensorimotor nerve lesion occurring within the canal of Guyon was made electrophysiologically. Magnetic resonance imaging demonstrated compression of the nerve within the canal by a ganglionic cyst, which was confirmed by surgical intervention. Ulnar nerve entrapment at the wrist is uncommon and diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In our case, we experienced the double compression syndrome of the ulnar nerve, which was diagnosed late after the surgical decompression of the cubital tunnel. Pearce et al 7 emphasized the importance of electrodiagnosis and stated that the electrodiagnostic study was sensitive in the detection of compression of the ulnar nerve at Guyon's canal. However, Osterman 8 reported that similar motor latencies were demonstrated between an isolated carpal tunnel syndrome and double compression syndrome and it seemed difficult to classify a single nerve lesion as the double crush syndrome by an electrodiagnostic study.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we experienced the double compression syndrome of the ulnar nerve, which was diagnosed late after the surgical decompression of the cubital tunnel. Pearce et al 7 emphasized the importance of electrodiagnosis and stated that the electrodiagnostic study was sensitive in the detection of compression of the ulnar nerve at Guyon's canal. However, Osterman 8 reported that similar motor latencies were demonstrated between an isolated carpal tunnel syndrome and double compression syndrome and it seemed difficult to classify a single nerve lesion as the double crush syndrome by an electrodiagnostic study.…”
Section: Discussionmentioning
confidence: 99%
“…The ulnar nerve is the second most severely impaired nerve in compression syndromes of the upper limb, and proximal involvement in the elbow is much more common (2,4,5) .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of ulnar nerve lesions shows variation due to the complex anatomical course of the nerve at its most distal sites, which hinders semiological and electrophysiological interpretation, resulting in diagnostic challenge (4,5) . In Guyon's canal, the ulnar nerve can be compressed along its course, producing sensory, motor or mixed deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothenar muscle may be spared in a distal lesion of the deep motor branch. A MRI may help exclude the presence of a mass lesion (Pearce et al, 2009) and an axial MRI at the level of the metacarpal bones is useful for detecting denervation of the intrinsic hand muscles (Andreisek et al, 2006).…”
Section: Ulnar Nervementioning
confidence: 99%